Technological Resources in Modern Higher Education - N. A. Astashova; S. L. Melnikov; A. P. Tonkikh; V. L. Kamynin (Russian State Vocational Pedagogical University, 2020)
Introduction. Modern high school should serve the needs of an innovative knowledge society based on the humanistic ideas, the introduction of digital pedagogy, the inclusion of didactic innovations into the educational process and the active use of practical-oriented technologies.The aim of the present article is to present and analyse the technological resources of higher education, revealing the educational potential of project training, smart technologies and event-based pedagogy.Methodology and research methods. The methodological framework of the present research is based in the humanistic, system and activity approaches, reflecting the essence of the development of modern education. The main methods involve the analysis and generalisation of the theory and practice of interactive technologies, studied by foreign and Russian scholars.Results and scientific novelty. The trends towards the modernisation of higher education and the factors of achievement of higher quality of preparation of students for professional activity are determined. The technological resources are considered as a key component of education and professionalisation of the future specialist. Project technology is highlighted as an advanced technology in education, as it accumulates cognitive practices, which stimulate the solution of cognitive problems; encourages and intensifies autonomous activities; provides an opportunity to visually and fully present the product of educational work. Students' educational purposes in the project are formulated and described: acquisition of actual knowledge, self-assessment experience and expert assessment; development of research skills; portfolio development.Smart education technologies create the following unique opportunities for training: activation of the complex of students' cognitive and creative abilities, prompt response to changes in the external environment; formation of practical personality skills to interact on social networks, to communicate in distance education, to work with electronic information resources, to create and manage personal knowledge databases, etc.Event-based education is demonstrated as a resource of open and free education and as a process of students' unique and fascinating creative work, which is created by the joint efforts of teachers and students.The diffusion of interactive technologies and ICT tools in higher education is changing the organisation of training and the quality of the educational environment, taking into account the principles of cooperation and openness, gaining flexibility and personal orientation.Practical significance. The rapid process of continuous technological improvement of the entire range of life activities, latest advances in the field of electronics and growing flows of open-access information significantly change the content of vocational education and its methodological tools. A prerequisite for the productive use of technological resources in the educational process is their adaptation to the main tasks in higher education, which aim to prepare a person for real and future life, to solve pressing socio-economic and sociocultural issues facing society.